The Application of the ECHR Judgements and Decisions by the Court of the Eurasian Economic Union (Theses) - Esenova, Valentina (Research Papers, 2018)
The paper explores some aspects of the Court of the Eurasian Economic Union’s activities and the prospects of its development among several other independent international courts.The Eurasian Economic Union (The EAEU) is an international organization for regional economic integration. Its bodies include the Court that operates on a permanent basis. The theses deal with some aspects of the EAEU Court practice of the application of the ECHR decisions on some complex legal issues. The conclusion substantiates the idea of mutual respect of courts as well as the importance of an integrated legal and economic space.